CORPUS-BASED APPROACHES TO STUDYING THE JADID MOVEMENT’S CONTRIBUTION TO THE DEVELOPMENT OF EARLY UZBEK MEDIA (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This review article examines how corpus-based methods (digital text analysis, diachronic corpora, keyword and collocation analysis) have recently been applied to the study of the Jadid movement and its contribution to the development of early Uzbek media. Drawing on both methodological literature in corpus linguistics and empirical studies of Jadid publications, the article argues that corpus approaches provide new empirical evidence clarifying the linguistic, semantic, and discursive innovations introduced by the Jadids. Key findings show that Jadid texts feature high frequencies of terms such as education / enlightenment, progress / reform, nation / people, and deploy a mix of classical and emerging modern Uzbek vocabulary; collocation and concordance patterns reveal consistent thematic clusters around modernization, social reform, and cultural identity. The review highlights strengths of corpus-based media historiography – transparency, reproducibility, quantitative support – as well as challenges (corpus representativeness, OCR quality, diachronic annotation). Finally, the article outlines prospects for advancing research on early Central Asian media through expanded corpora, tagged Uzbek corpora, and semantic shift detection.